In Vitro Monocyte/Macrophage Phagocytosis Assay for the Prediction of Drug‐Induced Thrombocytopenia. Issue 1 (23rd January 2019) - Narayanan, Padma Kumar; Li, Nianyu
Abstract: Phagocytosis of platelets by monocytes and macrophages is a primary mechanism of platelet clearance in vivo and has been increasingly implicated in playing an important role in thrombocytopenia mediated by monoclonal antibodies intended for therapeutic purposes. In the present article, we describe an in vitro flow cytometry assay to assess the effect of antibody‐mediated platelet phagocytosis by monocytes. Freshly isolated platelets were labeled with a fluorescent probe, 5‐chloromethylfluorescein diacetate (CMFDA) and then co‐cultured with isolated peripheral blood mononuclear cells (PBMCs) from the same donor in the presence of increasing concentrations of a monoclonal antibody drug. After incubation, an increase in CMFDA fluorescence intensity of CD14 positive monocytes was evaluated by flow cytometry as an assessment for drug‐mediated platelet phagocytosis by monocytes. The assay has been evaluated using both human and cynomolgus monkey cells for the prediction of drug‐induced thrombocytopenia. © 2019 by John Wiley & Sons, Inc.